2006
DOI: 10.1007/s00774-006-0710-3
|View full text |Cite
|
Sign up to set email alerts
|

Short-term and long-term site-specific effects of tennis playing on trabecular and cortical bone at the distal radius

Abstract: Mechanical loading during growth magnifies the normal increase in bone diameter occurring in long bone shafts, but the response to loading in long bone ends remains unclear. The aim of the study was to investigate the effects of tennis playing during growth at the distal radius, comparing the bone response at trabecular and cortical skeletal sites. The influence of training duration was examined by studying bone response in short-term (children) and long-term (young adults) perspectives. Bone area, bone minera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
45
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(51 citation statements)
references
References 51 publications
6
45
0
Order By: Relevance
“…Our findings in tennis players with the lowest weekly dedication (TP2) concur with earlier studies (Bass et al 2002;Ducher et al 2006). For example, (Ducher et al 2006) using DXA found similar side-to-side differences for BMC at the epiphyseal side of the radius in prepubertal tennis players (22 boys and 6 girls analyzed conjointly) who played at least twice a week compared to adult recreational tennis players (16 and 13%, for children and adults, respectively).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…Our findings in tennis players with the lowest weekly dedication (TP2) concur with earlier studies (Bass et al 2002;Ducher et al 2006). For example, (Ducher et al 2006) using DXA found similar side-to-side differences for BMC at the epiphyseal side of the radius in prepubertal tennis players (22 boys and 6 girls analyzed conjointly) who played at least twice a week compared to adult recreational tennis players (16 and 13%, for children and adults, respectively).…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies in our laboratory showed that professional tennis players who started tennis practice before puberty had 20% higher bone mineral content (BMC) and lean mass in the dominant compared to the non dominant arm and 10-15% greater bone mineral density (BMD) in lumbar and femoral subregions (Calbet et al 1998;Olmedillas et al 2010;Sanchís-Moysi et al 2009). Similar asymmetries, but of lower magnitude, have been reported in young tennis players (Bass et al 2002;Ducher et al 2006Ducher et al , 2009Sanchis-Moysi et al 2010). However, it remains unknown what is the role played by training frequency in the skeletal and soft-tissue adaptations elicited by training in young tennis players.…”
Section: Introductionsupporting
confidence: 59%
See 2 more Smart Citations
“…7 Several sports cause high training load during practice and thus act positively on bone accrual during growth, such as soccer, tennis and rugby. [8][9][10][11] However, the effects on bone mineral variables caused by sports participation performed in hypogravity during adolescence still remain unclear, 10,12 mainly because previous studies failed to control for the burden of important potential confounders in early life, such as training load and biological maturation. 12 In terms of bone mass gain, the pubertal period is responsible for significant accrual of bone mass in both boys and girls.…”
Section: Introductionmentioning
confidence: 99%